Projected changes in mean temperature and total precipitation and climate suitability of cassava (Manihot esculenta) in major growing environments of India - SOMAN, SABITHA; BYJU, G; SREEKUMAR, J (The Indian Journal of Agricultural Sciences, 2016)
Cassava (Manihot esculenta Crantz) is an important food crop of India cultivated in an area of 228 000 ha for food, feed and fuel, contributes to food security, equity, poverty alleviation and environmental protection. This study examined the projected climatic changes in the major cassava growing environments of India and also calibrated and evaluated the EcoCrop model to study the impact of 2030 climate on cassava climate suitability in the major growing environments of India. The current climate and future climate projections of 22 GCMs from the SRES-A1B emission scenario were used for the study. The projected change in annual mean temperature and total annual precipitation in the major growing areas ranged from 0.9 to 1.2ºC and from 6.8 to 112.4 mm, respectively. The calibrated data were used to drive the EcoCrop model to find out the suitability of current and future climatic conditions. The change in suitability for all the 22 GCMs used was calculated on pixel basis and the mean suitability change indicate that cassava is actually positively impacted in the current growing areas of India with -2.2 to 15% changes in climate suitability. This study concluded that cassava is potentially highly resilient to future climatic changes and it can become a future crop in India, where other crops would fail due to climate change.